Validation of an immunoassay method for the determination of traces of carbaryl in vegetable and fruit extracts by liquid chromatography with photodiode array and mass spectrometric detection - Nunes, G. S S; Marco, M. P.; Ribeiro, M. L.; Barcelo, D. (Elsevier B.V., 1998)
A competitive enzyme-linked immunosorbent assay (ELISA) method for carbaryl quantitation in crop extracts was validated by liquid chromatography (LC) with diode array detection (DAD). For this purpose, six crops (banana, carrot, green bean, orange, peach and potato) were chosen for recovery and reproducibility studies. The general sample preparation included extraction with methanol followed by liquid-liquid partitioning and clean-up on Celite-charcoal adsorbent column of the vegetable extracts. ELISA samples consisted of a diluted LC extract in assay phosphate buffer (pH 7.5). The potential effect of methanol in these samples was evaluated. It was observed that a maximum content of 10% methanol present in the assay buffer could be tolerated without expressive losses in the ELISA performance. Under these conditions, a IC50 similar to 1.48 mu g l(-1) was obtained. A minimum matrix effect with a 1:50 dilution of the methanolic extracts in assay buffer was noticed, except for green bean samples that inhibited completely the assay. For the vegetable extracts, the ELISA sensitivities varied from 3.9 to 5.7 mu g l(-1), and good recoveries (82-96%) with R.S.D.s ranging from 5.7 to 12.1% were found. An excellent correlation between the LC-DAD and ELISA techniques was obtained. The confirmation of the carbaryl in less concentrated samples was achieved by LC-mass spectrometry interfaced with atmospheric pressure chemical ionisation. The [M + H](+)= 202 and [M + H-57](+)=145 ions, equivalent to the protonated molecular and l-naphthol ions, respectively, were used to carbaryl identification in these samples. (C) 1998 Elsevier B.V. B.V. All rights reserved.
Keywords: vegetables; fruits; food analysis; carbaryl; pesticides